The Effect of Motivation and Learning Style on Student PAI Learning Outcomes at SMP Negeri 02 Piobang Kec. Payakumbuh - Azahra, Fatma; Charles, Charles; Afrinaldi, Afrinaldi; Wati, Salmi; Riski Pratama, Andy (FONDATIA, 2024)
This study was conducted to address the low motivation and learning styles of class VIII students in participating in learning activities at SMP Negeri 02 Piobang, Payakumbuh District. Issues observed include students not paying attention during lessons, lack of focus, and leaving school early. The research aimed to: (1) examine the influence of learning motivation on PAI (Islamic Education) learning outcomes; (2) analyze the effect of learning styles on PAI learning outcomes; and (3) investigate the combined effect of motivation and learning style on PAI learning outcomes. The study employed a quantitative ex post facto approach, with data collected through questionnaires and multiple-choice tests. A simple random sampling technique was used to select participants from the student population. Multiple linear regression analysis revealed the following results: (1) Learning motivation significantly influences PAI learning outcomes, as indicated by a p-value < 0.05 and t-value of 13.527 > 1.99345; (2) Learning style also significantly affects PAI learning outcomes, shown by a p-value < 0.05 and t-value of 14.279 > 1.99345; and (3) Both factors together significantly influence PAI learning outcomes, with an F-value of 101.516 > 3.124 and p-value < 0.05.